2014
DOI: 10.1021/nl404268f
|View full text |Cite
|
Sign up to set email alerts
|

Near-Surface Strain in Icosahedra of Binary Metallic Alloys: Segregational versus Intrinsic Effects

Abstract: A systematic structural analysis of FePt, CuAu, and Au icosahedral nanoparticles is presented. The uncovered particles are prepared by inert gas condensation and thermally equilibrated through in-flight optical annealing. Aberration-corrected high-resolution transmission electron microscopy reveals that the crystal lattice is significantly expanded near the particle surface. These experimental findings are corroborated by molecular statics simulations that show that this near-surface strain originates from bot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 41 publications
5
29
0
Order By: Relevance
“…17 large lattice expansion of up to 10% close to the surfaces. 20 Ab-initio calculations show that the change in surface energies is a function of the oxygen chemical potential. 21 In-situ TEM experiments show a change of the particle surface as surrounded by either CO or O 2 environments.…”
mentioning
confidence: 99%
“…17 large lattice expansion of up to 10% close to the surfaces. 20 Ab-initio calculations show that the change in surface energies is a function of the oxygen chemical potential. 21 In-situ TEM experiments show a change of the particle surface as surrounded by either CO or O 2 environments.…”
mentioning
confidence: 99%
“…We assigned atomic columns to hcp-Co [0001] and Co 3 C phases accordingly (Fig. 4b), which con rms again the co-existence of Co and Co 3 C. A t of two dimensional (2D) Gaussians to the intensity of distribution of the atomic columns was used to acquire the precise column coordinates, which improved the resolution to sub-angstrom 38,46 . The perpendicular layer spacings were determined locally from those tted coordinates and then averaged for each shell (d 12 , d 23 , d 34 ...) ( Supplementary Fig.…”
Section: Resultsmentioning
confidence: 94%
“…2D Gaussian tting of TEM image. The 2D Gaussian t to the intensity distribution of the atomic columns from HRTEM image was conducted using the StatSTEM V3.0 code run on MATLAB (R2015b) 46 . More details were showed in Supplementary Fig.…”
Section: Methodsmentioning
confidence: 99%
“…It is reported that multiply twinned icosahedrons usually contain intrinsic strain with compression stress in the core and tension stress in the shell [32,33], where the lattice tends to gradually expand from inner to outer layers [32,34]. As mentioned above, Cu 5 FeS 4 can crystallize into three phases: high cubic phase (Fm3m, a = 5.49 Å), intermediate cubic phase (Fm3m, a = 10.95 Å), and orthorhombic phase (Pbca, a = c = 10.95 Å, b = 21.862 Å) [20,29].…”
Section: The Formation Mechanisim Of Core-shell Structuresmentioning
confidence: 99%
“…It is of interest to note that intrinsic inhomogeneous strains are reported to exist in small particles (especially the multiply twinned particles) [36,37], which will induce chemical segregation [34,38], structural fluctuations and phase instability [39], and so on. On the other hand, the intrinsic strains of nano-particles can be utilized to improve the stability of core-shell structures and regulate crystal structures, which may be used to design core-shell and other exotic nanostructures.…”
Section: The Formation Mechanisim Of Core-shell Structuresmentioning
confidence: 99%